Catecholaminergic Polymorphic Ventricular Tachycardia - Mohamed Abbas; Chris Miles; Elijah Behr (Arrhythmia & Electrophysiology Review)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmia syndrome characterised by adenergically mediated bidirectional and/or polymorphic ventricular tachycardia. CPVT is a significant cause of autopsy-negative sudden death in children and adolescents, although it can also affect adults. It is often caused by pathogenic variants in the cardiac ryanodine receptor gene as well as other rarer genes. Early identification and risk stratification is of major importance. β-blockers are the cornerstone of therapy. Sodium channel blockers, specifically flecainide, have an additive role. Left cardiac sympathetic denervation is playing an increasing role in suppression of arrhythmia and symptoms. Concerns have been raised, however, about the efficacy of implantable cardioverter defibrillator therapy and the risk of catecholamine driven proarrhythmic storms. In this review, we summarise the clinical characteristics, genetics, and diagnostic and therapeutic strategies for CPVT and describe recent advances and challenges.